PARTISIPASI MASYARAKAT DALAM PERUMUSAN KEBIJAKAN PUBLIK - Hikmawati, Hikmawati (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2013)
This article is trying to explore participation, one of the crucial Good Governance elements, as one concept which is elaborated not only as a merely participating, but also containing an effort to control awareness to truly immerse in the whole political process. There should be a real red line between participating per se and participating with awareness. Just participation may be a form of pseudo participation, which is established on the basis of mobilization. Participation with awareness, on the other hand, is more contributing to create fundamental changes in political process. In the context of participation, this sort of understanding is really crucial. Besides, this article analyzes any forms of public participation in formulating policies to govern Indonesia, particularly the locals. Whether or not they have a direct correlation with wider public interests, they have to be proportionally appreciated, particularly after the application of local autonomy. This also plays a criticism towards the just participation in Indonesia, which has caused Indonesia to be left behind by developed countries due to the latter amazing political awareness. Development may be well running by depending on the government strength, but the result will be much better when the development fully obtain public support and participation.